Efforts Towards the Development of New Antitubercular Agents: Potential for Thiolactomycin Based Compounds - Ahmed Kamal; Shaik Azeeza; M. Shaheer Malik; Ahmad Ali Shaik; Maddamsetty V. Rao (Frontiers Media S.A., 2008)
Development of new chemotherapeutic drugs is the need of the hour to improve tuberculosis control, particularly in the developing world. In the last fourty years no new compound has been brought to the market for the treatment of tuberculosis. However, in recent years there is an enhanced activity in the research and development of new drugs for TB. Some compounds are presently in clinical development, while others are being investigated pre-clinically in an attempt to explore new molecules for the target based treatment of TB. Simultaneously some new targets are being identified and validated for their practical usefulness. Structures based on thiolactomycin could have considerable potential in the development of target based anti-TB agents. The present review provides an overview of the drugs that are being clinically used and the compounds that are in advanced stages of clinical as well as preclinical studies. We have also attempted to highlight the efforts that are being made in the development of new molecules based on thiolactomycin as lead compound, including studies from this laboratory.